Sociological Jurisprudence as the Basis for Online Arbitration in Non-Litigation Alternative Dispute Resolution in Medical Dispute Cases - Hadi Zulkarnain (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This study explores the application of sociological jurisprudence in online arbitration as a non-litigation alternative for resolving medical disputes in Indonesia. Sociological jurisprudence integrates the law with the social dynamics of society, which in the Indonesian context is reflected in the culture of consensus decision-making. Online arbitration utilizes technology to facilitate efficient and fair dispute resolution. This study proposes that the principle of consensus, in line with the Fourth Principle of Pancasila, can be implemented in online arbitration to achieve win-win solutions between patients and doctors or hospitals. Understanding that online arbitration is akin to consensus decision-making, led by a neutral and impartial arbitrator, is crucial for applying this concept in medical practice. The findings of this study indicate that online arbitration meets the need for a swift, precise, and mutually beneficial dispute resolution process for all parties involved.